2022
DOI: 10.1097/prs.0000000000009921
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Metacarpal Subsidence following Trapeziectomy and Its Relationship to Clinical Outcomes

Abstract: Methods: An institutional review board–approved retrospective review of patients who underwent trapeziectomy and ligament reconstruction and tendon interposition (LRTI) was conducted. Patient demographics, visual analogue scale pain scores, grip strength, pinch strengths, and radial and palmar abduction were collected. The trapezial space ratio (TSR) was measured by the scaphometacarpal distance divided by the length of the capitate. Subsidence [(postoperative TSR − preoperative TSR)/preoperative TSR] was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…found that subsidence occurs in patients with trapeziectomy and concurrent LRTI up to 16 weeks post-operative, and does not result in any differences in post-operative pain, range of motion, or grip and key/pinch strength [25]. Thus, it is unclear whether these adjunctive procedures confer additional benefit in preventing subsidence.…”
Section: Discussionmentioning
confidence: 99%
“…found that subsidence occurs in patients with trapeziectomy and concurrent LRTI up to 16 weeks post-operative, and does not result in any differences in post-operative pain, range of motion, or grip and key/pinch strength [25]. Thus, it is unclear whether these adjunctive procedures confer additional benefit in preventing subsidence.…”
Section: Discussionmentioning
confidence: 99%
“…Meyers et al. (2023) reviewed 141 trapeziectomies with ligament reconstruction and tendon interposition (LRTI) and reported that subsidence occurs in all patients after trapeziectomy and LRTI but that the degree of subsidence does not correlate with postoperative symptoms. Molin et al. (2022) retrospectively examined 91 thumbs in 65 patients after a mean of 10 years after trapeziectomy with and without LRTI.…”
Section: Re: Lui H Galbraith Jg Meyers K Bindra R Lee Sk Biomechanica...mentioning
confidence: 99%
“…In a number of studies directly comparing pain, function and quantitative subsidence, there is no consistent evidence that proximal migration of the first metacarpal is associated with continued symptomatology or poor function. Meyers et al (2023) reviewed 141 trapeziectomies with ligament reconstruction and tendon interposition (LRTI) and reported that subsidence occurs in all patients after trapeziectomy and LRTI but that the degree of subsidence does not correlate with postoperative symptoms. retrospectively examined 91 thumbs in 65 patients after a mean of 10 years after trapeziectomy with and without LRTI.…”
mentioning
confidence: 99%